Floral anatomy of Peristethium leptostachyum (Loranthaceae). - Robles, Alejandra (2016)
Peristethium leptostachyum is a hemiparasite species of the family Loranthaceae, distributed in Colombia, Costa Rica, Ecuador, Peru, Venezuela and Panama. Previously treated as Struthanthus leptostachyus, the species was recently transferred to Peristethium together with other species of Cladocolea and Struthanthus. The present research describes the inflorescence and floral morphoanatomy of Peristethium leptostachyum, detailing the structure of the androecium and gynoecium and the processes of microgametogenesis and megagametogenesis, thus allowing comparison with Struthanthus and Cladocolea. Flowering material was collected in February and August 2012, in Santa María, Boyacá, Colombia. Histological sections were prepared and stained with astrablue-fuchsin and floral dissections were performed under a stereomicroscope. Peristethium leptostachyum shares inflorescence characters with Cladocolea (determinate inflorescence, ebracteate terminal flower), but also with Struthanthus (pairs of triads along the axis, deciduous bracts and actinomorphic flowers). The flowers of P. leptostachyum from Santa María are clearly hermaphrodites with androecium and gynoecium fully developed. This observation contradicts the description by Kuijt who reported this species to be dioecious. The androecium was observed to be similar to that of Struthanthus vulgaris, with a glandular tapetum and simultaneous microsporogenesis; in contrast, Cladocolea loniceroides has a periplasmodial tapetum and successive microsporogenesis. The gynoecium of P. leptostachyum, like that of Cladocolea, Struthanthus and Phthirusa, has a unilocular ovary with a mamelon and arquesporial tissue isoriented towards the style, which in turn is solid and amyliferous. Peristethium leptostachyum is similar to Cladocolea loniceroides and differs from Strutanthus vulgaris in presenting multiple embryo sacs and an unlignified pelvis (hipostase). The presence of a solid stylar canal is proposed as a synapomorphy of the tribe Psittacanthinae. Given that P. leptostachyum shares characters with both Cladocolea and Struthanthus generic placement cannot be clearly determined on the basis of anatomical evidence. Phylogenetic studies that include representative species of all three genera are desirable to test hypotheses of monophyly. The sexual system observed here in P. leptostachyum is different from that reported by Kuijt and more studies are needed to identify the factors (geographic, ecological, etc.) that influence this variation.